Expression and purification of the recombinant human torsin A - Wu,Yan (Kansas State University, 2012)
Early-onset dystonia (EOTD, also known as DYT1 or Oppenheim’s dystonia is the most severe and common form of hereditary dystonia, a neurological disorder characterized by abnormalities in the control of movement. It is linked to the deletion of a single GAG codon in the gene DYT1 that leads to the loss of a single glutamic acid residue in the C-terminal region of the protein torsinA (ΔE-torsinA). It is not known how the GAG deletion alters the torsinA structure and function. In this thesis, the expression and purification of recombinant torsinA variants from E. coli is reported. Wild type torsinA is not soluble after its expression in E. coli, possibly due to misfolding caused by cysteine. We produced Cys-less torsinA, and established a purification procedure to produce this mutant torsinA. Furthermore, because of the critical role likely to be played by the C-terminal domain of torsinA that contains the glutamate deletion, we produced fragments encoding the C-terminal domain of torsinA, and attempted to purify it. However, we failed to obtain appreciable amount of active proteins by both of the strategies. A novel SUMO fusion technology was also used in this study. We demonstrated that SUMO, when fused with torsinA variants, was able to enhance its expression and solubility in E. coli. A satisfactory yield of the fusion protein was successfully purified. Once we get appreciable quantities of folded torsinA variants, it is our future goal to study their function by using biochemical and high-resolution structural approaches.
Expression and purification of the recombinant human torsinA
Keywords: TorsinA; Purification; Biochemistry (0487)